2004
DOI: 10.1051/0004-6361:20040486
|View full text |Cite
|
Sign up to set email alerts
|

Milliarcsec-scale radio structure of a matched sample of Seyfert 1 and Seyfert 2 galaxies

Abstract: Abstract.We have obtained mas-scale resolution very long baseline interferometry (VLBI) images of a sample of Seyfert 1 and Seyfert 2 galaxies at 5 GHz (wavelength, λ = 6 cm). The Seyferts of the two types were chosen to be matched in several orientation-independent properties, primarily in order to rigorously test predictions of the unified scheme. We detected all the 15 objects that we observed. In this paper we describe the observations and data reduction procedures, and present the VLBI radio images as wel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 36 publications
2
53
2
Order By: Relevance
“…Column 1: source name; Column 2: distance to the source assuming a cosmology with H 0 = 75 km s −1 Mpc −1 and q 0 = 0; Column 3: total flux density on arcmin-scale at 1.4 GHz (NVSS: Condon et al 1998); Column 4: total flux density on arcsec scale at 5 GHz; Column 5: core flux density on arcsec scale at 5 GHz; Column 6: core flux density on mas scale at 5 GHz; Column 7: radio power on arcmin-scale at 1.4 GHz (NVSS: Condon et al 1998); Column 8: total radio power on arcsec scale at 5 GHz; Column 9: core radio power on arcsec scale at 5 GHz; Column 10: core radio power on mas scale at 5 GHz; Column 11: logarithm of the projected linear size on mas scale at 5 GHz. (Ulvestad & Wilson 1984a, 1984b); (9) 1997 July, VLBA 8.4 GHz measurement (Mundell et al 2000); (10) (Unger et al 1984); (11) Our (Lal et al 2004) measurements; (12) Ulvestad & Wilson 1989;(13) Pedlar et al 1993;(14) Kukula et al 1995;(15) Ulvestad & Wilson 1984a. 1992a) at 1.7 and 2.3 GHz. They reported that compact radio structures are much more common in Seyfert 2 than in Seyfert 1 galaxies in the far-infrared-selected samples, as well as in the combined mid-infrared and optically selected sample.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Column 1: source name; Column 2: distance to the source assuming a cosmology with H 0 = 75 km s −1 Mpc −1 and q 0 = 0; Column 3: total flux density on arcmin-scale at 1.4 GHz (NVSS: Condon et al 1998); Column 4: total flux density on arcsec scale at 5 GHz; Column 5: core flux density on arcsec scale at 5 GHz; Column 6: core flux density on mas scale at 5 GHz; Column 7: radio power on arcmin-scale at 1.4 GHz (NVSS: Condon et al 1998); Column 8: total radio power on arcsec scale at 5 GHz; Column 9: core radio power on arcsec scale at 5 GHz; Column 10: core radio power on mas scale at 5 GHz; Column 11: logarithm of the projected linear size on mas scale at 5 GHz. (Ulvestad & Wilson 1984a, 1984b); (9) 1997 July, VLBA 8.4 GHz measurement (Mundell et al 2000); (10) (Unger et al 1984); (11) Our (Lal et al 2004) measurements; (12) Ulvestad & Wilson 1989;(13) Pedlar et al 1993;(14) Kukula et al 1995;(15) Ulvestad & Wilson 1984a. 1992a) at 1.7 and 2.3 GHz. They reported that compact radio structures are much more common in Seyfert 2 than in Seyfert 1 galaxies in the far-infrared-selected samples, as well as in the combined mid-infrared and optically selected sample.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 gives the measured flux densities and the spectral indices for our Seyfert sample. Mrk 348 and Mrk 231 show radio variability (Lal 2002). Mundell et al (2009) using VLA at 8.4 GHz have shown that five sources from their sample of 12 optically selected, early-type Seyfert galaxies show radio variability.…”
Section: Source Spectral Indicesmentioning
confidence: 94%
See 3 more Smart Citations